Peningkatan Mutu Pembelajaran Seni Tari di Sekolah Dasar - Zora Iriani (Fakultas Bahasa dan Seni UNP, 2008)
The aim of the art education is to develop both the students’ physical and mental states maximally. The dance art in particular, appear to be one of the subjects tought in elementary school. This subject is aimed at enabling the students toacquire art learning. The art experience is expected to give support in the education efforts.that is why the curriculm of the dance art does not demand the students to be famous or to be professional dancer although there must be some talented student in this area. Keywords: development, quality, learning, dance art.